2022
DOI: 10.1152/japplphysiol.00793.2021
|View full text |Cite
|
Sign up to set email alerts
|

Six-month longitudinal tracking of arterial stiffness and blood pressure in young adults following SARS-CoV-2 infection

Abstract: Introduction: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) can increase arterial stiffness 3-4 weeks following infection, even among young, healthy adults. However, the long-term impacts of SARS-CoV-2 infection on cardiovascular health and the duration of recovery remains unknown. Purpose: The purpose of this study was to elucidate potential long-lasting effects of SARS-CoV-2 infection on markers of arterial stiffness among young adults during the six months following infection. Methods: Assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 99 publications
5
13
1
Order By: Relevance
“…Likewise, arterial stiffness was also shown to be inversely related to time since diagnosis. These findings are in agreement with the findings of a recent follow up study by Szeghy et al ( 29 ), which showed improvement in carotid-femoral PWV over the first 6 mo from diagnosis in young otherwise healthy adults who had COVID-19. Although no significant relationship with time since diagnosis was found for central BP in the current study, Szeghy et al ( 29 ) reported an improvement in central systolic BP and mean BP at 6 mo compared with 1 mo after diagnosis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Likewise, arterial stiffness was also shown to be inversely related to time since diagnosis. These findings are in agreement with the findings of a recent follow up study by Szeghy et al ( 29 ), which showed improvement in carotid-femoral PWV over the first 6 mo from diagnosis in young otherwise healthy adults who had COVID-19. Although no significant relationship with time since diagnosis was found for central BP in the current study, Szeghy et al ( 29 ) reported an improvement in central systolic BP and mean BP at 6 mo compared with 1 mo after diagnosis.…”
Section: Discussionsupporting
confidence: 93%
“…These findings are in agreement with the findings of a recent follow up study by Szeghy et al ( 29 ), which showed improvement in carotid-femoral PWV over the first 6 mo from diagnosis in young otherwise healthy adults who had COVID-19. Although no significant relationship with time since diagnosis was found for central BP in the current study, Szeghy et al ( 29 ) reported an improvement in central systolic BP and mean BP at 6 mo compared with 1 mo after diagnosis. Collectively, these findings provide evidence for a potential transient impact of COVID-19 on indices of cardiovascular health in young adults.…”
Section: Discussionsupporting
confidence: 93%
“…This is similar to the data from middle-aged adults that showed cardiac BRS was lower <3 mo compared with >3 mo from diagnosis ( 20 ). Together, these findings align with previous data indicating a time-course improvement in blood pressure and arterial stiffness in young adults ( 21 , 22 ) and suggest that similarly, any potential autonomic changes following COVID-19 are transient in young, otherwise healthy adults.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, we may have expected to observe concomitant reductions in sympathetic activity and BP if the current study had included older adults recovering from SARS‐CoV‐2. The reductions in resting BP in the present study could be due to improvements in endothelial function (Ratchford et al, 2021) and/or decreased arterial stiffness (Szeghy et al, 2021), as assessed by carotid‐femoral pulse wave velocity (Szeghy et al, 2022) over 6 months recovery in this cohort. No changes in estimated cardiac output were observed over time in this cohort, further supporting the potential role of changes in endothelial function and/or arterial stiffness in observed reductions in BP in the months following SARS‐CoV‐2 infection.…”
Section: Discussionmentioning
confidence: 62%